ROLE OF MELATONIN IN EXPRESSION OF MALONDIALDEHYDE ON MICROGLIA CELLS OF RAT INDUCED HEAD INJURY - Nasution, Khairul Iksan (BALI MEDICAL JOURNAL; Vol 4 No 2 (2015), 2015)
Background: brain injury is condition that harm human life. This study examines the application of melatonin in reducing oxidant status and barriers to the formation of cerebral edema in a rat brain injury model. The main purpose of this study is to prove the role of melatonin on the expression of Malondialdehyde (MDA) and histological injury in a rat head injury model. Methods: This study was a randomized experimental posttest only control group design. This experimental was carried out on male Sprague Dawley strain Rattus novergicus, aged of 10-12 weeks, and weight of 300 g. Rat brain injury model was performed based on Marmarou (1994).1 Histology were observed using hematoxilen-eosin staining and immunohistochemistry, MDA was assessed using antibodies specific to each MDA protein. Observation and calculation of immunohistochemistry studies were also performed. Results: In this study, histological observation area covers an area of bleeding, number of immune-competent cells and the diameter of the arteries. Histology observation results showed that there is a significant reduction in diameter of arterial blood vessels of the brain injury tissue. Immunohisto-chemistry results showed that there is a significant reduction of MDA expression amount microglia cells of brain injury tissue. Conclusion: From this study, it can be concluded that Melatonin is a potent hydrogen peroxide scavenger that reduce the production of MDA.
Keywords: human; life; staining; scavenger